Narrative essay writing in Xitsonga home language : a case of grade 10 learners in Mopani District, Limpopo Province, South Africa - Mahlaule, Predict Khanimamba (My University, 2024)
This research reveals that learners encounter difficulties when writing essays. The purpose of this study is to investigate Grade 10 learners’ inability to write narrative essays at Sekgosese East Circuit, Mopani District in the Limpopo Province. The research methodology utilized in carryng out this study is qualitative approach, an interpretive case study, wherein purposive and non-probability sampling method are applied in the sampling of the two Xitsonga home language teachers together with the six learners’ narrative essays. Furthermore, the semi-structured interview and documents analysis are used to collect data and through didactic analysis approach, the collected data is analyzed. The findings of this study indicate the common errors committed by learners in writing essays, which compromise their abilities to write narrative essays and recommend essay writing strategies that can be used to improve learners’ essay writing abilities. The researcher applied for ethical clearance from the University of Limpopo’s Research and Ethics Committee (TREC) to conduct the study, through the submission and approval of a research proposal. The researcher further requested permission to conduct the study from the Limpopo Provincial District Director of Education and the selected school principals by sending letters to them. Since most learners are minors, for them to take part, permission was sought from their parents. The researcher also sent consent forms to be signed by parents and teachers indicating that they allow their children to take part in the study.
Thesis (M.Ed. (Language Education)) -- University of Limpopo, 2024
Keywords: Narrative essays; Writing skills; Coherence; Cohesion; Writing process; Xitsonga essays -- South Africa -- Limpopo Province; Xitsonga language -- Writing